Endometrial L-selectin ligand is downregulated in the mid-secretory phase during the menstrual cycle in women with adenomyosis - Tsung-Hsuan Lai; Fung-Wei Chang; Jun-Jie Lin; Qing-Dong Ling (Elsevier, 2018)
Objective: Defects in L-selectin ligand (LSL) expression have been reported to cause implantation failure, but little is known about LSL expression in adenomyosis. This study evaluates LSL expression throughout the menstrual cycle in women with adenomyosis. Materials and methods: Endometrial samples were obtained from reproductive-aged women with adenomyosis who underwent hysterectomy. A total of 42 endometrial biopsies were included. There were 12 women in proliferative phase, 10 in early-secretory phase, 9 in mid-secretory phase, and 11 in late-secretory phase. Immunohistochemistry, western blotting, and RT-PCR were performed to evaluate LSL expression. A non-parametric Kruskal-Wallis one-way analysis of variance with multiple comparisons was performed to examine differences among menstrual phases. Results: Immunohistochemistry analysis with MECA-79 shows that LSL is expressed with weak intensity in the endometrium in all phases. In the luminal epithelium, MECA-79 reactivity increased from the proliferative to the late-secretory phase but decreased in the mid-secretory phase. There were significant differences in the mean histological scores (HSCOREs) among the proliferative, early-secretory, and late-secretory phases (p < 0.05). Five LSL genes were detected in the adenomyotic endometria: PODXL, EMCN, CD300LG, GLYCAM1, and CD34. The mRNA expression of LSL genes occurred differentially among phases. Moreover, PODXL differed significantly among phases (p < 0.05). Conclusions: LSL expressions were downregulated in the luminal epithelium of adenomyotic endometria in the mid-secretory phase. The mRNA expressions of LSL genes also had differential expression patterns throughout the menstrual cycle, especially for PODXL. Our study showed that adenomyosis may cause abnormalities of LSL production in the mid-secretory phase, which may contribute to impaired endometrial receptivity and implantation failure. Keywords: Adenomyosis, Endometrium, L-selectin ligand